Hadith-Based Religious Coping Model on Tawakkal: A Neuropsychological Analysis of Stress Reduction Mechanisms - Achmad Yaqub; Firdaus Firdaus; Deliana Putri; Widya Astuti (Hamidah: Jurnal Ilmu Hadis, 2025)
The increasing prevalence of work-related stress, social uncertainty, and cognitive overload in modern society demands the development of religious coping strategies that are not only normative but also have a testable scientific basis, especially since there is still a lack of a conceptual model that integrates religious teachings with neuropsychological evidence. This study aims to formulate a conceptual model of religious coping based on tawakkal (religious trust), based on an analysis of the authenticity and meaning structure of hadiths, and to synthesize empirical evidence from the psychology of religion and neuroscience to explain the neuropsychological mechanisms of stress reduction associated with the practice of faith and submission to God. The study employed an integrative study design that included an analysis of the text of the ṣaḥīḥ hadith using sanad-matn criteria, a review of the psychology of religion literature from major databases such as PubMed and Scopus, and a synthesis of neuroimaging findings and stress biomarkers using a thematic synthesis approach. The results indicate that tawakkal functions as an active coping strategy that involves realistic cognitive appraisal, restructuring meaning by shifting perceptions of personal burden, strengthening a sense of control through belief in causal regularity, and internalizing adaptive expectations. Neuropsychological synthesis shows that religious practices consistent with the concept of tawakkal are associated with decreased amygdala activity, which reduces threat perception, increased prefrontal cortex involvement in emotion regulation, and activation of the reward system, which produces calm and adaptive motivation. These mechanisms contribute to decreased rumination, greater affective stability, and increased psychological resilience, thus making tawakkal a significant potential basis for developing religious coping theory and values-based psychological interventions.